THE IMPORTANCE OF CARDIORESPIRATORY FITNESS AND PHYSICAL ACTIVITY AMONG ADULTHOOD STAGES—REVIEW - Dan Alexandru SZABO (Studia Universitatis Babeş-Bolyai: Educatio Artis Gymnasticae, 2021)
Introduction: Adulthood is a period of development and transformation, though it may not be as dramatic as childhood and adolescence. Physical changes, for example, from youth to adolescence, are transformative. The body proliferates and develops secondary sexual characteristics as adolescence progresses. Exercise training for the elderly has been linked to a variety of health benefits, including a reduction in cardiovascular mortality. Changes in the balance of the cardiac autonomic nerves result in an increase or relative innervation of the vagus nerve, an explanatory mechanism that may be involved after exercise. Regular physical activity has also been linked to improving mental health (for example, reducing stress, anxiety, and depression). Mental health is critical for preventing and managing cardiovascular disease, but it also impacts other chronic diseases (such as diabetes, osteoporosis, hypertension, obesity, cancer, and depression). Conclusions: Finally, this review unifies the relationship between physical activity, cardiorespiratory health, and adulthood across the life span. In adulthood, changes in daily physical activity have a significant impact on overall health and well-being. As people’s corporeal and psychological health care deteriorates with age, regular physical activity becomes crucial for well-being.